Pemanfaatan Media Sosial Instagram Sebagai Media Komunikasi, Informasi, Dan Promosi Di UMKM Minuman Herbal Berkah Setia - Darwati Darwati; Saputri, Aqilla Aura Anggreini; Uliyah, Uni Masrochati; Putri, Erlina Meidiana; Aktamiati , Wulan; Qurniawati, Rina Sari (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The community service activity entitled "Use of social media as a means of communication, information, documentation and promotion in the Blessings of Faith herbal drink business" aims to implement the university's tridharma, namely Community Service. The purpose of this activity is to provide information regarding the use of social media Instagram for small businesses and provide training on the use of Instagram so that its use can later be implemented in marketing activities for the red blessing red ginger business. The method used in this activity is direct observation of the Red Blessings Faithful ginger business by conducting direct interviews and documenting product photos and product manufacture which are then uploaded to Instagram media. The final result of this service is the use of social media Instagram as a medium for communication, information, documentation and means of promoting each product produced and activities discussed by the Ginger Berkah Setia business unit including images and supporting information